1991
DOI: 10.1007/bf02513554
|View full text |Cite
|
Sign up to set email alerts
|

Combining pheromone‐baited and food‐baited traps for insect pest control: Effects of developmental period

Abstract: An age-structured population dynamics model is presented that incorporates pheromone-trapping and food-trapping as control methods for an insect pest. The model yields the following results. Low rates of pest survivorship allow lower trapping rates for control. Species with long developmental periods are easier to control than those with shorter developmental periods (other factors being equal) due to lower net survival. The rates of pheromone trapping alone for effective control are usually very high. The com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The three adult host states are: virgin females (V), fertilized females (F), and males (M); age classes are not distinguished in the adults and the numbers represent totals at a given time. The host-parasitoid system is assumed to be regulated by means of host larval competition for resources, as with the model of Barclay and Haniotakis (1991). The model consists of a set of difference equations with k host larval equations and three host adult equations.…”
Section: Assumptions and Equationsmentioning
confidence: 99%
“…The three adult host states are: virgin females (V), fertilized females (F), and males (M); age classes are not distinguished in the adults and the numbers represent totals at a given time. The host-parasitoid system is assumed to be regulated by means of host larval competition for resources, as with the model of Barclay and Haniotakis (1991). The model consists of a set of difference equations with k host larval equations and three host adult equations.…”
Section: Assumptions and Equationsmentioning
confidence: 99%
“…The mass trapping methods can be applied by traps of different constructions, which have to be set on the tree canopy. The traps are filled with different types of attractants and treated by insecticide, or they could be filled with attractant-insecticide water solution (Haniotakis et al, 1983;Barcley and Haniotakis, 1991;Bjeliš, 2006). Mass trapping has been reported to show better efficacy over bait sprays and it has lower cost of application especially human labour (Brumas and Haniotakis, 1987;Bumas et al, 1998;Delrio and Lentini, 1993;Bjeliš, 2006.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the chemical attractants used in the traps, comparative tests have shown that a combination of food and sex attractants in the same trap are more effective for control purposes than any attractant type alone (Haniotakis and Vassiliou-Waite, 1987). The same has been shown in computer simulations of the population dynamics of this pest (Barcley and Haniotakis, 1991).…”
Section: Introductionmentioning
confidence: 85%